Increased expression of inducible nitric oxide synthase and cyclo-oxygenase-2 in the airway epithelium of asthmatic subjects and regulation by corticosteroid treatment. Issue 5 (1st May 2001) - Redington, A E; Meng, Q-H; Springall, D R; Evans, T J; Créminon, C; Maclouf, J; Holgate, S T; Howarth, P H; Polak, J M
Abstract : BACKGROUND: Nitric oxide (NO) and prostanoids are mediators of vascular and bronchial tone that are postulated to be involved in asthma. Increased levels of both are found in asthmatic subjects and are synthesised by enzymes that have cytokine inducible forms: inducible NO synthase (iNOS) and cyclo-oxygenase-2 (COX-2), respectively. We hypothesised that the in vivo expression of iNOS and COX-2 in the airways would be increased in asthma, and that these cytokine inducible enzymes may represent targets for regulation by corticosteroid treatment. METHODS: Bronchial biopsy specimens were obtained from three groups of subjects: atopic asthmatics treated with β2 agonists alone (n=7), atopic asthmatics additionally receiving regular treatment with corticosteroids (n=8), and non-asthmatic control subjects (n=10). Expression of iNOS and COX-2 mRNA and immunoreactive protein was studied using in situ hybridisation and quantitative immunohistochemistry. RESULTS: Immunoreactivity and the hybridisation signal for iNOS and COX-2 were mainly localised in the airway epithelium. The proportion of epithelium immunostained was significantly greater in the non-steroid treated asthmatic subjects (iNOS 8.6 (1.8)%; COX-2 26.3 (4.6)%) than either the steroid treated asthmatics (iNOS 3.4 (1.0)%, p=0.009; COX-2 13.0 (0.6)%, p=0.0015) or the non-asthmatic controls (iNOS 4.2 (0.9)%, p=0.018; COX-2 11.6 (0.6)%, p=0.0003). Similarly, the hybridisation signal was stronger in the non-steroid treated group of asthmatic subjects than in the other two groups. CONCLUSIONS: These findings highlight the potential role of the airway epithelium both as a contributor to the inflammatory process in asthma and as a target for inhaled corticosteroid treatment in this disease.